Reasons for living and health behaviors in university students with and without intrafamily violence, (according to public and private universities) of the city of Lima - Huerta Rosales, Rosa E. (2019)
The variables of health behaviors and reasons for living were analyzed, according to public and private universities, with and without intrafamily violence in a sample of 495 students, to whom a data sheet and Lifestyles Questionnaires (CEVJU-r Lima) were applied in university students and Reasons for Living in Young Adults (RFL-YA). There is a significant relationship between health behaviors and reasons for living. Violence, health behaviors, physical activity and sports and sleep organization are associated with future expectations, coping beliefs, positive self-evaluation and peer relations; the personal will and the companions help to face difficult environments. At the public university, physical activity and sports, organization of resting-state activities and free time are associated with future expectations, coping beliefs, positive self-evaluation, peer relations and family when there is violence, becoming protective behaviors. In public and private universities, without violence, family relationships have high personal and social significance. Unlike men, women, without violence, show meaningfull health behaviors and reasons for living. Family can represent a protective or a risk factor in the prevention of suicide and health condition.